2018
DOI: 10.1111/jhn.12610
|View full text |Cite
|
Sign up to set email alerts
|

International survey on growth indices and impacting factors in children with food allergies

Abstract: Background: Elimination diets required for the management of food allergies increase the risk for poor growth in children. Currently, no worldwide data exist on this topic and limited published data exist on the impact of atopic comorbidity, type of allergy and foods eliminated on growth. We therefore set out to perform a worldwide survey on growth and impacting factors in food allergic children. Methods: A prospective growth survey was performed of children (aged 0-16 years) on an elimination diet with confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 36 publications
(53 reference statements)
2
39
1
Order By: Relevance
“…In addition, patients with CV-and/ or soya-FPIES have an increased risk of reacting to solid food(s) 82,83 ( The impact on paediatric growth as a result of dietary elimination for food allergies has been well documented. [86][87][88][89][90][91] A recent international survey on growth indices in children with food allergies (n = 430) found that children with non-IgE-mediated allergies or mixed IgE-and non-IgE-mediated food allergy had lowered heightfor-age Z scores than those with IgE-mediated food allergy alone, confirming findings from other studies. 86,87,92,93 Children with FPIES should have their growth closely monitored including measurements of both weight and length.…”
Section: Long-termsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, patients with CV-and/ or soya-FPIES have an increased risk of reacting to solid food(s) 82,83 ( The impact on paediatric growth as a result of dietary elimination for food allergies has been well documented. [86][87][88][89][90][91] A recent international survey on growth indices in children with food allergies (n = 430) found that children with non-IgE-mediated allergies or mixed IgE-and non-IgE-mediated food allergy had lowered heightfor-age Z scores than those with IgE-mediated food allergy alone, confirming findings from other studies. 86,87,92,93 Children with FPIES should have their growth closely monitored including measurements of both weight and length.…”
Section: Long-termsupporting
confidence: 75%
“…The impact on paediatric growth as a result of dietary elimination for food allergies has been well documented . A recent international survey on growth indices in children with food allergies (n = 430) found that children with non‐IgE‐mediated allergies or mixed IgE‐ and non‐IgE‐mediated food allergy had lowered height‐for‐age Z scores than those with IgE‐mediated food allergy alone, confirming findings from other studies .…”
Section: Managementsupporting
confidence: 69%
“…Children with non-IgE-GI-FA can experience poor growth, which may be attributed to increased losses due to intestinal malabsorption and/or to limited food intake due to feeding difficulties, which are found in up to 30% of these patients [ 64 , 168 ]. Consequently, both weight [ 64 , 168 , 169 ] and height [ 169 ] may be affected. Deficient intake of indispensable micronutrients, including vitamin D, calcium, zinc, selenium [ 170 , 171 , 172 , 173 ], has also been reported, negatively impacting bone health [ 173 ].…”
Section: Managementmentioning
confidence: 99%
“…In children with food allergy, allergy to cow's milk is a risk factor for poor growth, and the presence of 2 or more food allergies has been associated with reduced height for age compared with controls. 28,[32][33][34] In addition, children with allergy to cow's milk consume less calcium than is recommended compared…”
Section: Growthmentioning
confidence: 99%